Dostępność cyfrowa jako standard e-usług polskiej administracji publicznej – zarys problemu .......... 107 - Grzegorz Firlus, Jakub (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
DIGITAL ACCESSIBILITY AS A STANDARD OF E-SERVICES IN POLISH PUBLIC ADMINISTRATION – INTRODUCTORY REMARKSAn e-service provided by public administration must, like any other product, meet certain requirements. The study attempts to assess whether e-services of the Polish public administration are compliant with the digital accessibility standard. For the purposes of the study, the validity of the accessibility standard in the legal order was verified. An effort was made to systematize the consequences of violating the pattern of digitally accessible behavior. The option of transplanting the administrative procedural norms as a tool for measuring the legality of competence behavior that is digitally inaccessible was also considered.